2005
DOI: 10.1063/1.2039943
|View full text |Cite
|
Sign up to set email alerts
|

Electron density and ionization dynamics in an imploding z-pinch plasma

Abstract: The time-dependent radial distributions of the electron and ion densities during the implosion phase of a gas-puff z-pinch plasma are determined from measurements of continuum radiation, as well as time-dependent collisional-radiative analysis of the observed particle ionization history in the plasma. It is shown that during the 140-ns-long time interval close to the end of the ϳ620-ns-long implosion phase, the total imploding-plasma mass increases by ϳ65%, found to be consistent with the continuous ionization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…In order to minimize the experimental uncertainties in the observed intensities, the data for each line were averaged over five to eight experiments, and two to four population ratios for each charge state were used. In the C-R analysis, the ratios were calculated for several values of , and the range of chosen was based on continuum radiation measurements [51]. As an example, we present in Fig.…”
Section: Determination Of the Electron Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…In order to minimize the experimental uncertainties in the observed intensities, the data for each line were averaged over five to eight experiments, and two to four population ratios for each charge state were used. In the C-R analysis, the ratios were calculated for several values of , and the range of chosen was based on continuum radiation measurements [51]. As an example, we present in Fig.…”
Section: Determination Of the Electron Temperaturementioning
confidence: 99%
“…This plasma region was found to be the hottest and most dense part of the plasma. In this example, was determined both using population ratios within one charge state, and using ratios of levels from successive charge states, the latter with the proper detailed analysis [51], providing a higher accuracy.…”
Section: Determination Of the Electron Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of velocity is important to inferring the plasma kinetic energy, which can be the primary storage reservoir of j × B work accumulated over ∼100 ns during implosion and then provide plasma heating when thermalized at stagnation. While some studies have shown consistent energy balance between kinetic energy input and radiated output [15][16][17][18][19], others have proposed that additional physical processes may provide further plasma heating [20][21][22][23]. Doppler velocity measurements will help to test models and address this key physics issue for high-current pinches [24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the general interest of the B-field penetration, these data are also critical to solving the energy balance in a z-pinch plasma. Combining these data with other spectroscopic measurements of the electron temperature, density, and ion velocity, Gregorian et al [19][20][21] were able to demonstrate that ϳ85% of the energy imparted to their z pinch comes from the J ϫ B force with the remainder coming from the Joule heating.…”
Section: Magnetic Field Measurementsmentioning
confidence: 94%